ChemInform Abstract: Development of Chemoselective Photoreduction of Nitro Compounds under Solar Light and Blue LED Irradiation. Issue 24 (2nd June 2014) - Zand, Zahra; Kazemi, Foad; Hosseini, Saber
Abstract TiO2‐P25 acts as reusable photocatalyst for the chemoselective reduction of nitroarenes.